2013
DOI: 10.1007/s10452-013-9434-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns of trait-based phytoplankton functional groups in two basins of a large, shallow lake (Lake Balaton, Hungary) with different trophic state

Abstract: The application of functional approaches in understanding phytoplankton community-level responses to changes in the environment has become increasingly widespread in recent years.Eutrophication is known to cause profound modifications in ecosystem processes, however, the underlying relationships between environmental drivers and phytoplankton diversity and functioning are complex and largely unknown. Therefore, in the present study we investigated and compared the temporal diversity patterns of phytoplankton f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…Negative relationships were present in 11.5% of cases, which means a decreasing ecosystem functioning as trait diversity increased. As an explanation for this pattern, authors suggest that under some condi- tions one single productive taxa with particular traits might dominate, leading to low functional diversity coupled to high biomass (Pälffy et al, 2013;Santos et al, 2014). Unfortunately, none of the studies reviewed here explicitly tested the suggested mechanisms and remained purely conjectural.…”
Section: Biodiversity and Ecosystem Functioning Relationshipsmentioning
confidence: 93%
See 4 more Smart Citations
“…Negative relationships were present in 11.5% of cases, which means a decreasing ecosystem functioning as trait diversity increased. As an explanation for this pattern, authors suggest that under some condi- tions one single productive taxa with particular traits might dominate, leading to low functional diversity coupled to high biomass (Pälffy et al, 2013;Santos et al, 2014). Unfortunately, none of the studies reviewed here explicitly tested the suggested mechanisms and remained purely conjectural.…”
Section: Biodiversity and Ecosystem Functioning Relationshipsmentioning
confidence: 93%
“…The six studies can be separated into two categories: field and laboratory studies. The former includes four studies in which both trait-based diversity and ecosystem functioning data were obtained from natural conditions (Vogt et al, 2010;Pälffy et al, 2013;Santos et al, 2014;Fontana et al, 2017). In the other two studies, diversity was directly manipulated under highly controlled conditions in the laboratory (Shurin et al, 2014;Steudel et al, 2016).…”
Section: Studiesmentioning
confidence: 99%
See 3 more Smart Citations